The Brazilian Innovation Award: Analysis of assessment instrument validity and reliability - Eleutério Delesposte, Jamile; de Oliveira Vale Coutinho, Mariana; Baptista Narcizo, Ramon; Cardoso, Rodolfo; Lopes da Silva, Carlos Eduardo (Brazilian Journal of Operations & Production Management, 2019)
Goal: This article presents an analysis of the validity and reliability of the assessment instrument used in the 2016–2017 Brazilian Innovation Award. Design/Methodology/Approach: This study used multivariate analysis techniques on the data from 2,651 companies. Two hypotheses were tested. The first (H1), related to reliability, used Pearson’s Correlation and Cronbach’s alpha. The second hypothesis (H2), related to validity, used Confirmatory factor analysis (CFA). Results: The instrument is reliable and valid and is an important mechanism for the assessment of the maturity of innovation management. Limitations of the investigation: One of the constructs can still be improved in future studies and applications, although it has demonstrated acceptable levels of reliability and validity. Practical implications: The combined use of the constructs “organizational dimensions” and “innovation outcomes” proved to be an accurate conceptual model for assessing the maturity level of innovation management in organizations. Originality/Value: The instrument is a robust diagnostic instrument and, with appropriate adaptations, it can be replicated and used in other contexts and countries, providing international comparative studies.